1/2D SnO2 nanowires on MnO2 nanosheets hybrid architecture for reducing fire hazards of epoxy nanocomposites. (April 2018) - Liu, Jiajia; Wang, Wei; Yuen, Richard K.K.; Gui, Zhou; Hu, Yuan
Abstract: SnO2 nanowires decorated MnO2 nanosheets hybrids, were prepared and incorporated into epoxy resins to improve the flame retardancy and inhibite the smoke in combustion. SnO2 -MnO2 hybrids shows significant improve in flame retardancy, fire toxicity and thermal properties of epoxy nanocomposites, compared to neat epoxy and nanocomposites with a single SnO2 or MnO2 . The char residues and glass transition temperature of the epoxy/2 wt% SnO2 -MnO2 nanocomposite were remarkably increased. The peak heat release rate of EP/2 wt% SnO2 -MnO2 was significantly decreased by 62.9% than that of pure epoxy. TG-FTIR results that the concentration of organic volatiles of epoxy was significantly reduced and the toxic CO was suppressed after incorporating SnO2 -MnO2 . The physical barrier for SnO2 -MnO2 hybrids and the synergism between the catalysis effect of SnO2 and MnO2 can improve the flame retardancy of epoxy resin.